Determinants of employee well-being among manufacturing employees in Kulim Hi-Tech Park, Kedah - Omar, Siti Nur Zahirah; Kamalbahrin, Habibah Maisarah; Malik, Sabriena Fakhira; Fadzil, Farah Hasyira; Jazmi, Nur Balqis; Mukhtar, Nurul Farah Nasrin (Journal of Islamic, Social, Economics and Development, 2026)
Employee well-being plays a significant role in ensuring a good, productive, and sustainable workforce, especially for those operating in the manufacturing industry where the workers may experience challenging working conditions. The purpose of this study is to investigate the relationships between work-life balance, job stress, working environment, workload, low compensation, and well-being of manufacturing employees in Kulim Hi-Tech Park, Kedah. In this study, quantitative, cross-sectional, and correlational research designs would be adopted. The sample population will be operator level employees in multinational manufacturing organizations within Kulim Hi-Tech Park. Based on the Krejcie and Morgan sampling table, about 380 respondents will be chosen through convenience sampling technique. Data will be gathered using a structured questionnaire administered online through a five-point Likert scale. Items in the questionnaire are drawn from the measurement scales and literature reviewed. The collected data will be analyzed using Statistical Package for the Social Sciences software. Descriptive statistics and Cronbach’s alpha would be employed to describe the characteristics of respondents and test reliability of the instrument. Pearson correlation and multiple linear regression analysis will be done to examine the relationships between the selected workplace variables and employee well-being.